Environmental comfort in a classroom: analysis of the thermal perception of students in two regions and estimation of comfort zones - Lucas, Ruan Eduardo Carneiro (2017)
Understanding the thermal relationship between an individual and an environment is important when analyze how the existing conditions provide an efficient performance. Therefore, this paper aims to assess the environmental comfort in two classrooms in different regions, analyzing thermal perception and estimating a comfort zone. The analysis was held at a envirolment in the city of João Pessoa-PB and São Carlos-SP, Brazil. The experiment was conducted in three days, and the air temperature was manipulated 20.24 and 28 ° C. On each day questionnaires were about the temperature conditions, thus enabling a comparative analysis of the perceptions of the two cities. Therefore, it is concluded that the sample of students from the northeast region had a favorable thermal perception at higher temperatures, different sample analyzed in the Southeast, which showed a preference for lower temperatures. This result indicates that the adaptability of students in their respective regions influenced this perception.